Choose the optimum conditions for the simultaneous adsorption of the lead and cadmium ions orange pell as a adsorption surface. (Latakia University Journal -Basic Sciences Series, 2018)
The study investigated the possibility of removing heavy metal ions (Cd, Pb) from aqueous solutions using adsorption method on the citrus peel (orange), which is a solid waste available in abundance especially in the Syrian coast as well as easy to use at low cost. The optimal conditions for the simultaneous adsorption of the ions (Cd 2+, Pb 2+) on the surface of  orange peel (dry, soft) were determined.The concetration of ions was determined using (DPASV) method Which is characterized by Sensitivity and high accurawcy. The results showed that the optimum adsorption conditions were at pH = 5 , equleibrium time = 60 min, and the initial concentration is ( C0 = 50-200) ppm,The application of the Langmuir and Frienlish models showed that Frienlish model is best fited for expressing the adsorption of Pb ions on the surface of dry and soft orange peel and for expressing the adsorption of Cd ions on the surface of soft  orange peel , Langmuir model is best fited for expressing the adsorption of Cd ions on the surface of dry orange peel.The method applied its selected terms to realistic samples of processed and industrial waste water, which showed a unique response as a purification method for the water media.